Legal Consequences for Leasing Companies That do not Provide Funds in Accordance to the Initial Agreement - Agus Dwi Arifudin; Noor Fatimah Mediawati; M. Tanzil Multazam (Indonesian Journal of Law and Economics Review, 2018)
Leasing is an activity in the field of financing such as banks, but not banks in the form of providing capital goods that have option rights and a certain period of time. The research is expected to add insight and as an input for the community about legal issues and issues regarding lease agreements made by leasing financing institutions. The method used is a statute approach approach based on the current legislation, and a conceptual approach to reviewing the views and doctrines that develop in the field of legal science. Leasing companies that do not provide loan funds in accordance with the purchase lease agreement, according to Article 1320 of the Indonesian Civil Code, the agreement is legally flawed and can be canceled, and deemed to have never existed. Because in this agreement the objective conditions in Article 1320 of the Indonesian Civil Code are not fulfilled because they have committed fraud against the contents of the agreement.